PERSONALITY DEVELOPMENT, EDUCATION AND COMPETENCE AS BASIC ELEMENTS OF CREATIVITY - Gaveika, Artūrs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The task of modern technologies is not only to reproduce the obtained information, but also to motivate students to new knowledge, competence and creativity in a wider spectrum of a professional sphere. In this article the connection between education, development and competence in creation of a creative individual has been researched. The author comes to the main conclusion that the creative individual is based on the education and personal development throughout their lives through educational competence of teachers, creating individual and professional competences of a modern person as a base for creative personality.